Perfeksionisme dan Manajemen Waktu Sebagai Prediktor Perilaku Prokrastinasi Akademik pada Mahasiswa - Sari, Indah Novita; Lestari, Sri (Jurnal Online Psikogenesis, 2023)
Nurses are health workers who are always there in every hospital and are a benchmark for hospital health services, so this is a major concern that management should not ignore because it will have an impact on the organization. The purpose of this study was to explore relationship between meaning of work and organizational commitment in nurses mediated by job satisfaction. Respondents in this study were 214 nurses with a minimum working period of one year in the hospital. Data collection methods in this study use a scale of (1) The Work and Meaning Inventory (WAMI), (2) Organization Commitment Questionnaire (OCQ), and (3) Job Satisfaction Scale from Scale for the Measurement of Some Work Attitudes and Aspects of Psychological Well-Being. The result showed that meaning of work positively correlated to job satisfaction and organizational commitment. Moreover, job satisfaction positively effects organizational commitment. The results of data analysis using simple model 4 mediator analysis from PROCESS by Hayes (2012) show that job satisfaction plays a significant role as a partial mediation on the relationship between meaning of work and organizational commitment on nurses. This means that nurses have high job satisfaction don’t necessarily have high organizational commitment. Conversely, nurses who have low job satisfaction don’t necessarily have low organizational commitment. Therefore, the hospital needs to make a program to increase the meaning of the work that nurses have because it can have an impact on the organizational commitment of a nurse.